TRANSFORMASI MADRASAH DALAM SISTEM PENDIDIKAN NASIONAL - Supaat, Supaat (Jurnal Penelitian dan Evaluasi Pendidikan, 2013)
Undang-undang No.2 Tahun 1989 tentang Sistem Pen-didikan Nasional mengamanatkan madrasah ditransformasi dari lembaga pendidikan agama menjadi sekolah yang berciri agama Islam. Pada status yang baru madrasah harus bekerja keras memenuhi tuntutan stakeholders. Penelitian tentang transformasi Madrasah Aliyah (MA) ini menggunakan pendekatan kualitatif. Hasil penelitian adalah ada enam masalah yang diidentifikasi yaitu (1) kapasitas manajemen, (2) kurikulum, (3) keterbatasan SDM, (4) orientasi akademik, (5) ujian nasional, (6) otonomi daerah. Secara kelembagaan, MA ada tiga tipe, yaitu MA Plus, MA Salf Tafaqqubfiddin, dan MA dengan pembelajaran ke-agamaan lebih banyak. Ada tiga model yang diaplikasikan yaitu institusional sebagai model utama, model sain terintegrasi, dan model manajemen terpadu. Penerapan model tersebut perlu memperhatikan kesesuaian karakter, konteks, dan setting MA. Kata kunci: transformasi, madrasah, pendidikan Islam, tipologi model ______________________________________________________________ TRANSFORMATION OF MADRASAH IN NATIONAL EDUCATION SYSTEM Abstract According to 1989 Education System Act No. 2, and 1990 Government Regulation No. 28, Madrassas as edu-cational institutions have transform from educational religion to "Schools Characterized by the Islamic teachings". With this new status, the madrassas entered into a new phase of struggle, from their legal status into meeting the needs and the expectations of their stakeholders. In case of implementation of its transformation, the result of this qualitative – phenol-menology approach, there were identified six problems of MA: (1) management capacity, (2) curriculum, (3) limited human resources, (4) academic orientation and science dichotomy (5) national examination, and (6) local government autonomy. Institutionally there are three major types of MA: (1) MA plus, (2) MA Salaf – Tafaqquh fiddin, (3) MA enriched with religious teachings. Based on the problems identified and the types of MA put into consideration, three models are offered as the results of social action study, i.e. (1) institutional model – streaming model, (2) integrated science model, and (3) integrated management model. The result of this study is methodologically idiographic, and the compatibility of these models depend upon the appropriateness of the characters, context and setting of an MA. Keywords: transformation, madrasah, Islamic education, tipology, model